Perancangan Arsitektur Enterprise Menggunakan TOGAF (Studi Kasus: Desa Sukahaji) - Feriyanto, Yanuar; Budiman, Aprianda Alif; Maulidia, Laely Isna (CV. Graha Mitra Edukasi, 2024)
The Sukahaji Village Office is a government institution that operates in the Village in the Sukahaji District Majalengka. The Sukahaji Village Government has not implemented an Information System in carrying out its duties, this can be seen from the obstacles faced by the Village Government. The obstacle faced is the frequent hoarding of old data, making it difficult when it will be recorded again, in fact there is usually lost data that requires a system that can help data storage. The purpose of this research is to provide direction to be able to implement information systems for data storage. performance in the future, the method used in the development of enterprise architecture this time is the TOGAF ADM (The Open Group Architecture Framework) method using 3 (three) phases out of 9 (nine) phases, namely the Preliminary Phase, Architecture Vision Phase and Business Architecture Phase. This research will produce a blueprint and provide a roadmap using the elements contained in the TOGAF at the Village Office in order to implement the Sukahaji Village Office performance information system in the future.